Rewriting/reprising : plural intertextualities - Letissier, Georges (Cambridge Scholars, 2009)
This volume comprises sixteen essays, preceded by an introductory chapter focusing on the diverse modalities of textual, and more widely, artistic transfer. Whereas the first Rewriting-Reprising volume (coord. by C. Maisonnat, J. Paccaud-Huguet & A. Ramel) underscored the crucial issue of origins, the second purports to address the specificities of hypertextual, and hyperartistic (Genette, 1982) practices. Its common denominator is therefore second degree literature and art. A first section ...